FIBROMYALGIA: A literature review - Dr. Sharat Agarwal* (Innovative Journal of Medical and Health Sciences, 2020)
Objective: To inform Health care professionals about diagnostic evaluation and various mechanisms of this little known but otherwise complex and very common disorder encountered in the clinical practice called as Fibromyalgia and its potential problems with management strategies. Data source: I searched Pubmed, Medline using key words Fibromyalgia, MFPS and chronic widespread pain, medicines and Cochrane database of systematic reviews for exercises and psychological therapies in fibromyalgia. Conclusion/Recommendations: Establishing the diagnosis and instituting extensive treatment and rehabilitation program can greatly improve the prognosis of the patient. Keywords: Fibromyalgia, chronic widespread pain, myofascial pain syndrome, medication, exercises in fibromyalgia